Absenteeism management in Limpopo Provincial Legislature - Tladi, Raisibe Florinah (University of Limpopo, 2017)
Absenteeism remains a challenge in government entities, especially if it is measured in monetary terms. Government loses a number of hours through employees who are officially or unofficially away from work. The high absenteeism is created by a number of factors, amongst which leave policy gaps and poor management systems can cited. Therefore this study expected to investigate the management of absenteeism in Limpopo Provincial Legislature. A qualitative research approach was used to collect data through semi-structured interviews. One of the major findings in the study is that there is a lack of communication between line-managers and human resources section. Departments still work in silos and hence some employees exploit their leave benefits. The study recommends that communication strategies in the Limpopo Provincial Legislature should be effectively implemented and policy gaps in relation to leave benefits should be reviewed.
Thesis (MPA.) -- University of Limpopo, 2017
Keywords: Absenteeism; Government Employees; Poor management system; Limpopo Provincial Legislature; Absenteeism (Labor); Absenteeism (Labor) - Law and legislation